Factors Associated with 12-Month Psycho-Active Substance Use among Police Officers in Kano Metropolis, Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Substance use is a widely recognized and pressing public health issue with grave consequences. It is important to prevent mishaps of substance use among the police.Aim:This study assessed the prevalence and factors associated with 12-month psycho-active substance use among police officers in Kano, Nigeria.Settings and Design:A cross-sectional study was conducted among police officers serving within metropolitan Kano.Methods and Materials:Pre-validated, adapted, semi-structured questionnaires were used to collect socio-demographic, work-related data and information on psycho-active substance use.Statistical Analysis Used:Multi-variate logistic regression modeling was used to determine factors associated with psycho-active substance use. All analyses were performed using STATA/IC 15.0.Results:Among 275 officers with a mean age of 35.1 ± 7.7 years, 14.9% (n= 41) recently used one or more psycho-active substances within the last 12 months, and tobacco was the most commonly used (n= 41, 100%). A lower likelihood of substance use was found among officers who were in their fifth decade of life (aOR = 0.29, 95% CI: 0.10–0.55), had tertiary education (aOR = 0.32, 95% CI: 0.14–0.77), were inspectors (aOR = 0.15, 95% CI: 0.16–0.61), were at the rank of ASP or higher (aOR = 0.58, 95% CI: 0.30–0.78), and had been in service between 16 and 20 years (aOR = 0.23, 95% CI: 0.11–0.65).Conclusion:Demographic and work-related characteristics influence the use of psycho-active substances among police officers in Nigeria. There is a need to revamp existing substance monitoring strategies to avoid catastrophic consequences of substance use among the society's gatekeepers.